Easing the assessment of emerging technologies in technology observatories. Findings about patterns of dissemination of emerging technologies on the internet. Issue 1 (2nd January 2018) - Carbonell, Javier; Sánchez-Esguevillas, Antonio; Carro, Belén
ABSTRACT: This paper considers the Web as a big data container that can be used by Technology Observatories and administrations to track emerging issues and more specifically emerging technologies. It considers information that is available on the Internet for free from different sources, and proposes a framework that can be useful to characterise them and to detect patterns of dissemination. This framework is made up of 30 metrics obtained from different kinds of sources (general web, patents, scholars …). Some of them are obtained directly as the number of hits retrieved by queries on a search engine, and other ones calculated by means of ratios. This paper contains the development of a complete case that utilises this framework to characterise emerging technologies included in the well-known Hype Cycle for Emerging Technologies, in this case the 2015 release 1 and to analyze patterns of dissemination of these technologies on the Internet.